Carboxylated Lignin-Based Adsorbents for the Efficient Separation of Mg2+From Aqueous Solutions Containing Li - Oyarce-Riveros, E (ELSEVIER, 2025)
This study focuses on the preparation of bio-based adsorbents composed of carboxylated lignin (LC) and potassium polyacrylate (PAS) to remove Mg2+ from aqueous solutions in the presence of Li+. The successful incorporation of carboxylate groups into lignin was achieved, which was corroborated by FT-IR. Acid-base titration allowed the quantification of 11.7 +/- 0.016 mmol of-COO-groups per gram of LC. Radical polymerization was used to obtain the bio-based adsorbents. The structural composition was corroborated by FT-IR and their porous morphology was evaluated by SEM and BET isotherms. The incorporation of LC improved the adsorption capacity of the material for Mg2+, increasing it by 60 %. The adsorption process was more accurately described by the PFO and Redlich Peterson kinetic models. The effective adsorption and the ion-exchange adsorption mechanism of Mg2+ on the adsorbents were confirmed by XPS, FT-IR, and SEM/EDS analyses. Furthermore, the adsorbent systems were shown to be able to adsorb Mg2+ in the presence of Li+, reducing the concentration ratio from 8:1 to 6:1. However, Mg2+ ions showed higher affinity for PAS-20 %-LC adsorbents (alpha Mg2+/Li+ = 3.78) as compared to PAS adsorbents (alpha Mg2+/Li+ = 0.50), confirming that the incorporation of LC into the adsorbent enhances Mg2+ adsorption. A preferential affinity toward divalent ions was observed in multicomponent solutions after the adsorption process. The Mg2+ adsorption capacity on PAS-20 %-LC remained almost constant even with increasing ionic strength of the system.